PENGARUH BREASTCARE TERHADAP PEMBENGKAKAN PAYUDARA PADA IBU NIFAS DI UPT PUSKESMAS CIPAMOKOLAN : Effect of Breastcare on Breast Engorgement in Postpartum Mothers at UPT Puskesmas Cipamokolan (Jurnal Kesehatan Siliwangi, 2022)
One of the problems that often appear during postpartum is breast engorgement. breast engorgement is closely associated with delayed breastfeeding, ineffective emptying of the breast and improper breastfeeding position in nursing mothers. This can be at risk to formula feeding due to painful and uncomfortable breasts so that exclusive breast milk coverage does not meet the coverage target. Non-pharmacological strategies that can be done to overcome the problem are breast care using olive oil. Breast care is an effort to prevent, reduce, and overcome breast swelling. Olive oil content can relax the breast muscles. The purpose of this report is to find out the effect of breastcare on breast swelling in postpartum mothers. The article search method using data based Google Scholar, Pubmeed and Cochrane Library according to the criteria of inclusion and exclusion. Meanwhile, the intervention method is carried out 2 times a day (morning and evening) with a duration of 10-15 minutes for 7 days using olive oil. The results of the report from the assessment of breast swelling using the Six Point Engorgement Scale (SPES) before and after the intervention showed a significant difference with a 4-scale reduction. It can be concluded that breast care by using olive oil affects breast swelling in postpartum mothers.